Pengaruh Pemahaman Perpajakan Tarif Pajak Dan Sanksi Pajak Terhadap Kepatuhan Wajib Pajak UMKM - Akbar, Arya Zulfikar; Hardiansyah, Rian (Jurnal Ilmiah Raflesia Akuntansi, 2024)
This study assesses the hypothesis and produces empirical data regarding the impact of tax comprehension, tax rates, and tax penalties on MSME taxpayer compliance in Sumbawa Regency, West Nusa Tenggara Province. This research utilizes primary data obtained through questionnaires administered to micro, small, and medium enterprises (MSMEs) in Sumbawa Regency. This study utilizes convenience sampling, a non-probability technique that selects units based on their accessibility to the researcher. The study employs a sample of 100 respondents. We evaluated the hypothesis using partial least squares (PLS)-based structural equation modeling (SEM) in SmartPLS 3.2.9. The findings of this study indicate that understanding tax regulations and the enforcement of tax sanctions have a positive and significant effect on taxpayer compliance. Tax rates have a negative and significant impact on taxpayer compliance among SMEs in Sumbawa Regency, though this effect is partial. This research investigates the factors influencing tax compliance, particularly in the context of micro, small, and medium enterprises (MSMEs). An in-depth understanding of the factors affecting tax comprehension, tax rates, and tax penalties enables tax authorities to formulate more effective educational and socialization strategies to improve taxpayer compliance.